Gymnema sylvestre extract improves PCOS by altering the YAP1 protein in the mouse ovary via mitochondrial changes - Aruna Jangam; Rama Satya Sri Kotipalli; Samata Sai Patnaik; Bhavana Kasireddy; Swarna Kumari Gaja; Bojja Sreedhar; Mahesh Kumar Jerald; Anthony Addlagatta; Kathirvel Muralidharan (Elsevier, 2024)
Background: Gymnema sylvestre (Retz.) R.Br. ex Sm. is a medicinal herb used in Ayurvedic medicine to treat diabetes. Through promoting obesity and lowering insulin resistance, anti-diabetic herbs may be more effective in treating polycystic ovarian syndrome (PCOS). Recently, YES‐associated protein-1 gene (YAP1) has been reported to be a new susceptibility gene for PCOS in clinical studies. Hence, we evaluated the effects of hydroalcoholic G. sylvestre extract on regulating the YAP1 protein in PCOS mice injected with dehydroepiandrosterone (DHEA) by examining mitochondrial alterations in the ovary. Materials and methods: The DHEA-induced PCOS female C57BL6/J mice were treated with three doses of G. sylvestre and standard drug metformin. Study parameters include body weight gain, estrus cyclicity, glucose tolerance testing, serum hormone levels, lipid profiles, liver enzymes, and inflammatory cytokines. Electron microscopy, histological, and immuno-histochemical (IHC) analyses were used to determine the morphological changes of the ovary. IHC analysis was used to assess the expression of the YAP1 protein. Results: As compared with the control group, the G. sylvestre-treated groups showed decreased obesity, estrus irregularity, improved glucose metabolism, reduced AST and ALT values, hormonal abnormalities, and inflammatory cytokines (IL-6, IL-17, IL-23, TNF-α). Interestingly, metformin and G. sylvestre therapy reduced YAP1-positive cells in the ovary of DHEA-induced PCOS mice. Conclusion: These findings suggest that a higher concentration of G. sylvestre extract at 500 mg/kg improved mitochondrial architecture in the PCOS ovary via modulating the key pathogenic protein of PCOS, YAP1.